USE OF PLANT-BASED PESTICIDES CYMBOPOGON NARDUS AND MIMOSA PUDICA TO CONTROL RICE PESTS - Inri Wowor; Christina L. Salaki; Jimmy Rimbing (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the effect of using extracts of Cymbopogon Nardus L. and Mimosa Pudica extracts as controlling pests of rice plants. The results of the study showed that the use of extracts of Cymbopogon Nardus and Mimosa pudica was able to cause mortality, especially for the pest Leptocorisa acuta on rice plants. The chemical content of Cymbopogon Nardus is in the form of citronella essential oil consisting of siral compounds, citronella, geraniol, mirsena, nerol, farnesol methyl heptanol, and dipentene. The largest content is citronella, which is 35%, and geraniol, which is 34-40%.The chemical content of Mimosa pudica is in the form of a secondary metabolite called mimosin, as well as pipecholinic acid, tannins, alkaloids, saponins, triterpenoids, sterols, polyphenols and flavonoids. The presence of this chemical content underlies the use of M. invisa weed as a vegetable pesticide.Keywords: Cymbopogon Nardus, Mimosa invisa, pesticides, vegetable extractsAbstrakKajian ini bertujuan untuk mengetahui pengaruh pemanfaatan ekstrak ekstrak Cymbopogon Nardus L. danÂ  Mimosa Pudica sebagai pengendali organisme pengganggu tanaman padi. Hasil kajian menunjukkan bahwa pemanfaatan ekstrak Cymbopogon Nardus dan Mimosa pudica mampu terjadi mortalitas, khususnya pada hama Leptocorisa acuta pada tanaman padi. Kandungan bahan kimia Cymbopogon Nardus ini berupa minyak atsiri serai wangi terdiri dari senyawa siral, sitronela, geraniol, mirsena, nerol, farmesol methyl heptenol, dan dipentena. Kandungan yang paling besar adalah sitronela yaitu 35% dan geraniol sebesar 34-40%.Kandungan bahan kimia Mimosa pudica berupa metabolit sekunder yang disebut mimosin, serta asam pipekolinat, tannin, alkaloid, saponin, triterpenoid, sterol, polifenol dan flavonoid. Adanya kandungan bahan kimia inilah yang mmendasari pemanfaatkan gulma M. invisa sebagai pestisida nabati.Kata kunci: Cymbopogon Nardus, Mimosa invisa, pestisida, ekstrak nabati.